CARACTERIZAÇÃO FÍSICA E FÍSICO-QUÍMICA DE FRUTOS DE Eugenia dysenterica DC. ORIGINADOS EM REGIÃO DE CLIMA TROPICAL DE ALTITUDE - BUENO, Gustavo Hernandes; GUEDES, Mayara Neves Santos; SOUZA, Amauri Geraldo de; MADEIRA, Ana Paula Coelho; GARCIA, Eric Marsalha; TAROCO, Hosane Aparecida; MELO, Júlio Onesio Ferreira (Brazilian Journal of Biometrics, 2017)
The fruit of Eugenia dysenterica, popularly known as cagaita, belonging to the Myrtaceae family, is part of the group of fruits of the Cerrado, known and consumed mainly by native peoples of this region. The aim of this study was to evaluate the physical, physicochemical fruit three cagateiras progenies in three different municipalities belonging to the Cerrado region. We randomly sampled 20 fruits by entire progeny in the municipalities of Paraopeba, Prudente de Morais and Caetanópolis, located in the state of Minas Gerais, during the harvest of 2014. The evaluated traits were: transverse and longitudinal diameter (cm), seed number per fruit, pH, soluble solids and titratable acidity. It was possible to state that the originating fruits of Paraopeba county had the highest average in the weight and diameter with respect to originating from the matrix cagaiteira belonging to Prudente de municipalities of Morais and Caetanópolis, showing to be the most promising for future genetic improvements in the species.